Molecular analysis of a series of alleles in humans with reduced activity at the triosephosphate isomerase locus. - Watanabe, M. (1996)
Individuals with 50% of expected triosephosphate isomerase (TPI) enzyme activity have been previously identified in families during the screening of approximately 2,000 newborn children for quantitative variation in activity of 12 erythrocyte enzymes. The frequency of the trait was 9/1,713 individuals in the Caucasian population and 7/168 individuals among the African-American population studied. Genetic transmission of the trait was confirmed in all families. The frequency of the presumptive deficiency allele(s) at the TPI locus was greater than expected, given the reported incidence of clinical TPI deficiency. We report the molecular characterization of the variant alleles from seven African-American and three Caucasian individuals in this group of unrelated individuals. Three amino acid substitutions--a Gly-->Ala substitution at residue 72, a Val-->Met at residue 154, and a previously described Glu-->Asp substitution at residue 104--were identified in the Caucasian individuals. The substitutions occur at residues that are not directly involved in the active site but are highly conserved through evolutionary time, suggesting important roles for these residues in maintenance of subunit structure and conformation. The variant allele in the seven African-American individuals had nucleotide changes at positions -8 and -5 (5' of) from the transcription-initiation site. In three of these individuals, an additional T-->G substitution was detected in a TATA box-like sequence located 24 nucleotides 5' of the transcription-initiation site and on the same chromosome as the -5/-8 substitutions. Thus, molecular alterations at the TPI locus were detected in 10 unrelated individuals in whom segregation of a phenotype of reduced TPI activity previously had been identified.